“When Music Speaks”: Auditory Cortex Morphology as a Neuroanatomical Marker of Language Aptitude and Musicality - Turker, Sabrina; Reiterer, Susanne M.; Seither-Preisler, Annemarie; Schneider, Peter (Frontiers in Psychology, 2017)
Recent research has shown that the morphology of certain brain regions may indeed correlate with a number of cognitive skills such as musicality or language ability. The main aim of the present study was to explore the extent to which foreign language aptitude, in particular phonetic coding ability, is influenced by the morphology of Heschl’s gyrus (HG; auditory cortex), working memory capacity, and musical ability. In this study, the auditory cortices of German-speaking individuals (N = 30; 13 males/17 females; aged 20–40 years) with high and low scores in a number of language aptitude tests were compared. The subjects’ language aptitude was measured by three different tests, namely a Hindi speech imitation task (phonetic coding ability), an English pronunciation assessment, and the Modern Language Aptitude Test (MLAT). Furthermore, working memory capacity and musical ability were assessed to reveal their relationship with foreign language aptitude. On the behavioral level, significant correlations were found between phonetic coding ability, English pronunciation skills, musical experience, and language aptitude as measured by the MLAT. Parts of all three tests measuring language aptitude correlated positively and significantly with each other, supporting their validity for measuring components of language aptitude. Remarkably, the number of instruments played by subjects showed significant correlations with all language aptitude measures and musicality, whereas, the number of foreign languages did not show any correlations. With regard to the neuroanatomy of auditory cortex, adults with very high scores in the Hindi testing and the musicality test (AMMA) demonstrated a clear predominance of complete posterior HG duplications in the right hemisphere. This may reignite the discussion of the importance of the right hemisphere for language processing, especially when linked or common resources are involved, such as the inter-dependency between phonetic and musical aptitude.